Molecular Mechanisms of Cardiovascular Aging - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: The average lifespan of humans is increasing, and with it the percentage of people entering the 65 and older age group is growing rapidly and will continue to do so in the next 20 years. Within this age group, cardiovascular disease will remain the leading cause of death, and the cost associated with treatment will continue to increase. Aging is an inevitable part of life and unfortunately poses the largest risk factor for cardiovascular disease.CONTENT: We provide an overview of some of the molecular mechanisms involved in regulating lifespan and health, including mitochondria, telomeres, stem cells, sirtuins, Adenosine Monophosphate-activated Protein Kinase, Mammalian Target of Rapamycin and Insulin-like Growth Factor 1. We also provide future perspectives of lifespan and health, which are intimately linked fields.SUMMARY: Aging remains the biggest non-modifiable risk factor for cardiovascular disease. The biological, structural and mechanical changes in senescent cardiovascular system are thought to contribute in increasing incidence of cardiovascular disease in aging. Understanding the mechanisms contributing to such changes is therefore crucial for both prevention and development of treatment for cardiovascular diseases.KEYWORDS: cardiovascular aging, mitochondria, telomeres, sirtuin, stem cells